PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. PROVICES INDONESIA JAKARTA - Ardi Riskiyanto; Thamrin (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of compensation and motivation on work productivity at PT. Provices Indonesia Jakarta. both partially and simultaneously. The method used in this study is a quantitative method. The sampling technique used is saturated sampling, which uses a sample of 95 respondents. The data analysis technique used is statistical analysis with validity test, reliability test, classical assumption test, simple linear test, multiple linear regression test, correlation coefficient, determination coefficient, t test and F test. The results of the study showed that compensation has a significant effect on employee performance partially, indicated by the simple linear regression equation Y = 48.465 + 0.251 Xₗ where the beta coefficient value is positive, which means that if compensation increases, employee work productivity will also increase. This is evidenced by the hypothesis test obtained a calculated t value> t table or (3.514> 1.662) and is reinforced by the ρ value <Sig.0.05 or significance <0.05 (0.000 <0.05). Motivation has a significant effect on employee work productivity partially indicated by the simple linear regression equation Y = 21,400 + 0.686X₂ where the beta coefficient value is positive, which means that if work discipline increases, employee work productivity will also increase. This is evidenced by the results of the hypothesis test obtained a calculated t value> t table or (8,286> 1.662) and is strengthened by the ρ value <Sig.0.05 or a significance value <0.05 (0.000 <0.05). The results of the study of compensation and motivation on employee work productivity are indicated by the multiple linear regression equation Y = 122,981 + 0.072 Xₗ + 0.645 X₂. where the coefficient value is positive, which means that if compensation and motivation increase, employee work productivity will also increase. This is proven by the results of the simultaneous hypothesis test obtained the value of F count > F table (35.095 > 3.10) and strengthened by the significance value < 0.05 (0.000 < 0.05). The results of the coefficient of determination test of the compensation variable (Xₗ) and motivation (X₂) have an influence of 11.7% on employee work productivity at PT. Provices Indonesia Jakarta. Thus H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence between Compensation (Xₗ) and Motivation (X₂) on employee work productivity (Y).